2021
DOI: 10.3389/fpls.2021.773825
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Morphological, Physiological, Proteomics Analyses of Jujube Fruit Development Provide Insights Into Fruit Quality Domestication From Wild Jujube to Cultivated Jujube

Abstract: Jujube (Ziziphus jujuba) was domesticated from wild jujube (Z. jujuba var. spinosa). Here, integrative physiological, metabolomic, and comparative proteomic analyses were performed to investigate the fruit expansion and fruit taste components in a jujube cultivar ‘Junzao’ and a wild jujube ‘Qingjiansuanzao’ with contrasting fruit size and taste. We revealed that the duration of cell division and expansion largely determined the final fruit size, while the intercellular space in the mesocarp dictated the ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 39 publications
0
10
1
Order By: Relevance
“…Similar to leaf, up-regulated expression of ZjHK6 and ZjFK2 would promote hexose phosphorylation, inhibiting the accumulation of fructose and glucose in shaded fruits. Huang et al [51] believed that SPS and INV should be considered key enzymes that promote sugar accumulation in the jujube cultivar 'Junzao,' which is different from the findings in our study under low light conditions. This difference might be attributed to altered transcription levels of related genes that affect sugar accumulation, or it might be the result of cultivar differences.…”
Section: Shading Inhibited Sugar Accumulation In Fruitscontrasting
confidence: 99%
“…Similar to leaf, up-regulated expression of ZjHK6 and ZjFK2 would promote hexose phosphorylation, inhibiting the accumulation of fructose and glucose in shaded fruits. Huang et al [51] believed that SPS and INV should be considered key enzymes that promote sugar accumulation in the jujube cultivar 'Junzao,' which is different from the findings in our study under low light conditions. This difference might be attributed to altered transcription levels of related genes that affect sugar accumulation, or it might be the result of cultivar differences.…”
Section: Shading Inhibited Sugar Accumulation In Fruitscontrasting
confidence: 99%
“…ZJ is domesticated from wild, sour jujube. ZA has sourer, smaller, and less fleshy fruit, and it gradually evolved into ZJ with a sweet taste, large fruit, and more flesh after a long period of artificial or natural domestication [ 106 ]. Metabolomic analysis of 182 ZJ and 25 wild ZA germplasm resources identified 427 metabolites with chemical annotations, including 41 terpene metabolites, and 90 metabolites showed a decreasing pattern from wild ZA to ZJ, and the reduced metabolites were primarily rich in triterpenoids.…”
Section: Resultsmentioning
confidence: 99%
“…The above results suggest that these genes have an important effect on maintaining high AsA content during the early development of jujube fruit. There are two AsA synthetic pathways in jujube, and Huang’s study based on the proteomic level of jujube identified 15 proteins involved in the L-galactose pathway but no proteins related to the myo-inositol pathway ( Huang et al, 2021 ). However, notably, in our study, since the expression levels of the two isoforms of ZjMIOX genes and ZjGulLO gene in myo-inositol pathway was up-regulated from the ST3 (white-ripening stage) ( Figure 4 ), indicating that the inositol pathway may play a vital role in maintaining AsA accumulation at maturity.…”
Section: Discussionmentioning
confidence: 99%